The impact of moral norms on the creation of public expenditure law – the Polish experience - Tyniewicki, Marcin; Salachna, Joanna Małgorzata (The Opole Studies in Administration and Law, 2022)
The aim of this article is to determine the extent of dependence/relation between moral norms and public expenditure law established in Poland as well as to determine the impact of this law on the formation of citizenship. The following theses have been formulated by the Authors on the basis of elaborated diagram: firstly, moral norms, including social rules arising from universal Christian values, should directly and indirectly strongly influence legal regulations in the scope of public expenditure as well as education and citizenship; secondly and this is a reverse process – public spending may to a certain extend impact the content of moral norms. These theses have been verified on the basis of two pilot researches. Moreover, the article, due to its aim, analyses the formation of public expenditure law in the context of public choice theory and principal-agent problem as well as verifies social evaluation of the connection between the content of moral norms and selected decisions concerning public expenditure.